Zczvt Inverters With Magnetically Coupled Auxiliary Pole - da Silva Martins, Mário Lúcio (2010)
Existing Zero-Current Transition and Zero- Current Zero-Voltage Transition inverters provides favorable switching conditions for IGBT semiconductors increasing significantly the reactive energy of the converter. This situation off-set the benefits accomplished by abovementioned soft-switching techniques. This paper presents a novel family of Zero-Current Zero-Voltage Transition inverters that overcome this problem by using no resonant tank in the auxiliary circuit. It accomplishes the favorable soft-switching conditions with a magnetically coupled auxiliary voltage source which is derived directly from the inverter filter inductor. Theoretical analysis of the inverter operation is presented and it is verified experimentally from a 1kW, 40kHz, laboratory prototype. The obtained experimental results prove the reliability of the proposed family of ZCZVT inverters.